Analysis on the effects of turbulent inflow conditions on spray primary atomization in the near-field by direct numerical simulation. (May 2018) - Salvador, F.J.; S., Ruiz; Crialesi-Esposito, Marco; Blanquer, Ignacio
Highlights: A synthetic boundary condition for turbulence has been successfully implemented in the open source code DNS Paris-Simulator. Once implemented, the spray primary atomization process has been simulated for three cases with different levels of turbulence, quantified by the lengthscale and the turbulence intensity. Results from the simulations have been compared in terms of vorticity field, external non-perturbed length and intact core length which are directly related to the atomization level. Results reflect that atomization is greatly improved when the turbulence intensity and turbulence lengthscale are increased. The different atomization processes, occurring in different spray locations have been analyzed. Abstract: It is widely acknowledged that the development of sprays in the near-field is of primary importance for the spray formation downstream, as it affects both the spray angle, as well as the intact core length. In this frame, the present work aims to study the effects of turbulence inlet boundary condition on the spray formation by means of Direct Numerical Simulations on a real condition at low Reynolds number. To this extent, the code Paris-Simulator has been used, while a digital filter-based algorithm was used in order to generate synthetic turbulence at the inlet boundary condition. The influence of turbulence intensity and lengthscale on the atomization process has been studied and analyzed through 3 simulation for which these parameters have been varied. The results clearly highlight how the atomization is heavily affected by the inlet turbulence configuration. An analysis of the different atomizing conditions has been conducted, aiming to understand how the variation introduced by the inlet boundary condition on the velocity field is affecting the local atomization dynamics.